Analisis Sistem Jaringan Pipa Distribusi SPAM di Kecamatan Inuman Kabupaten Kuantan Singingi - Siswanto; Andy Hendri; Winda Indriani (Departemen Teknik Sipil, Fakultas Teknik Universitas Riau, 2022)
The population from year to year always increases based on population statistics as ell as with the geographical and topographical conditions of different villages in Inuman District, resulting in the coverage of distribution network system services by SPAM at certain points not getting services and causing conditions where not all people who have access to the distribution network have received services. can be served. Three villages still have not received drinking water supply services by the Inuman District SPAM, namely Sigaruntang, Banjar Nan Tigo and Bedeng Sikuran villages. Based on these conditions, it is necessary to analyze how the hydraulic conditions of the existing network are and alternative alternatives for the development of distribution pipelines are needed to improve distribution services to the community. Collecting data in the form of information needed for processing the modeling of the Inuman SPAM distribution network such as elevation data of the study area, demographics, network maps, pipe data (pipe diameter and pipe length). The methods used in this research are population projection analysis, water demand analysis, distribution pipe network model simulation using EPANET 2.2 software in the form of hydraulic simulations in the form of head loss, flow velocity. From the results of this study, population growth estimates use the arithmetic method, the amount of water demand at peak hours in 2040 is 23,599 liters/second. Analysis of the distribution network development system using EPANET 2.2 with QPeak 23,599 liters/second there is no pressure below the pressure criteria.